101 facts about goldfish - Barnes, Julia, 1955- (Milwaukee, WI : Gareth Stevens Pub., 2002)
Provides information about goldfish, how to care for them, and how to understand their behavior.
Includes bibliographical references (p. 31) and index.
Keywords: Goldfish -- Miscellanea -- Juvenile literature; Goldfish -- Miscellanea; Pets -- Miscellanea